Screening for hypogonadism: real‐world considerations. Issue 6 (November 2016) - Heald, Adrian; Jones, Richard; Khan, Adnan; Donnahey, Gemma; Downie, Paul; Duff, Christopher; Livingston, Mark
Abstract : Testosterone levels are increasingly being checked in primary care as awareness of the risks of male hypogonadism grows. The authors looked at what tests are performed in general practice in Cheshire to screen for hypogonadism and to rule out secondary hypogonadism.